Photosensitizer-free visible-light-promoted glycosylation enabled by 2-glycosyloxy tropone donors - Jing Zhang; Zhao-Xiang Luo; Xia Wu; Chen-Fei Gao; Peng-Yu Wang; Jin-Ze Chai; Miao Liu; Xin-Shan Ye; De-Cai Xiong (Nature Communications, 2023)
Abstract Photochemical glycosylation has attracted considerable attention in carbohydrate chemistry. However, to the best of our knowledge, visible-light-promoted glycosylation via photoactive glycosyl donor has not been reported. In the study, we report a photosensitizer-free visible-light-mediated glycosylation approach using a photoactive 2-glycosyloxy tropone as the donor. This glycosylation reaction proceeds at ambient temperature to give a wide range of O-glycosides or oligosaccharides with yields up to 99%. This method is further applied in the stereoselective preparation of various functional glycosyl phosphates/phosphosaccharides, the construction of N-glycosides/nucleosides, and the late-stage glycosylation of natural products or pharmaceuticals on gram scales, and the iterative synthesis of hexasaccharide. The protocol features uncomplicated conditions, operational simplicity, wide substrate scope (58 examples), excellent compatibility with functional groups, scalability of products (7 examples), and high yields. It provides an efficient glycosylation method for accessing O/N-glycosides and glycans.